Linezolid Inhibited Synthesis of ATP in Mitochondria: Based on GC-MS Metabolomics and HPLC Method. (16th October 2018) - Ye, Xuemei; Huang, Aifang; Wang, Xianqin; Wen, Congcong; Hu, Lufeng; Lin, Guanyang
Abstract : Linezolid has been widely used in serious infections for its effective inhibiting effect against multidrug-resistant gram-positive pathogens. However, linezolid caused severe adverse reactions, such as thrombocytopenia, anaemia, optic neuropathy, and near-fatal serotonin syndrome. In order to investigate the toxicity of linezolid, twenty-four Sprague-Dawley rats were randomly divided into: control group (n=7), low-group (n=8), and high-group (n=9). The rats of low-group and high-group were given by gavage with linezolid 60 and 120 mg/kg/day for 7 days, respectively. The serum concentration of linezolid was determined by high performance liquid chromatography (HPLC); blood metabolic change was analyzed by gas chromatography-mass spectrometer (GC-MS). Adenosine triphosphate (ATP) concentration in HepG2-C3A after being cultured with linezolid was determined by HPLC. The results showed that there were six metabolites and nine metabolites had statistical differences in low-group and high-group (P<0.05). The trimethyl phosphate was the most significant indicator in those changed metabolites. Except for d-glucose which was slightly increased in low-group, octadecanoic acid, cholest-5-ene, hexadecanoic acid, α -linolenic acid, eicosapentaenoic acid, 9, 12-Octadecadienoic acid, and docosahexaenoic acid were all decreased in low-group and high-group. ATP concentration was decreased in HepG2-C3A after cultured with linezolid. In conclusion, the toxicity of linezolid is related to its serum concentration. Linezolid may inhibit the synthesis of ATP and fatty acid.